Ensino de comparação: elaboração, aplicação e avaliação de uma proposta com uso de software educativo - Fonseca, Cintia Cássia (2016)
The crisis of the educational system of public schools in Brazil, demonstrated by the results of national assessments, is contrary to what is expected from the development of critical reasoning on young people. The focus on building a quality education is to enable the formation of citizens that promote effective problem solving. Therefore, it is necessary to teach students to think. In this perspective, the comparison is fundamental for any individual to establish relationships between ideas or consider relevant parts of a given context. Therefore, the comparison should be taught through planned teaching procedures. In the teaching of history, the exercise of comparison corresponds to an essential repertoire for the understanding of historical processes and the identification of continuities and ruptures between the present and the past. This study aimed at the development, implementation and evaluation of a proposal of comparison teaching. Participants were 18 students between 11 and 12 years of the 6th grade of elementary public school of São Paulo. The survey was conducted in a collective context, using school s computers. Participants performed individually the pre-test, comparison teaching program and the post-test. The pre-test data and the post-test were collected through a writing activity in which students should compare two historical facts. For the analysis, categories corresponding to the similarities and differences to be identified were set up. The results showed that, out of the 18 participants, 12 did more comparisons after going through the program. There was an increase in both comparisons of similarities and differences. The program achieved positive results since it favored the development of comparison skills for most of the participants. However, considering that the program did not have the expected effect on a number of students, it indicated the need for improvement in both aspects of programming and implementation conditions. The discussion of such aspects provides directions for further studies on comparison teaching